2011
DOI: 10.1002/ar.21491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Precaudal Elongation on Visceral Topography in a Basal Clade of Ray‐Finned Fishes

Abstract: Elongate body forms have evolved numerous times independently within Vertebrata. Such body forms have evolved in large part via changes to the vertebral column, either through addition or lengthening of vertebrae. Previous studies have shown that body elongation in fishes has evolved most frequently through the addition of caudal vertebrae. In contrast, however, body elongation in Polypteriformes, a basal clade of ray-finned fishes (Actinopterygii), has evolved through the addition of precaudal vertebrae; one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Ropefish are known to make terrestrial excursions (Sacca and Burggren, 1982;Pace and Gibb, 2011) and a recent study showed how terrestrially raised Polypterus senegalus can use their pectoral fins to effectively locomote on land (Standen et al, 2014). Erpetoichthys calabaricus has approximately twice as many precaudal vertebrae (100) as P. senegalus (45), while both genera have similar caudal vertebral numbers (Ward and Brainerd, 2007;Ward and Kley, 2012).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ropefish are known to make terrestrial excursions (Sacca and Burggren, 1982;Pace and Gibb, 2011) and a recent study showed how terrestrially raised Polypterus senegalus can use their pectoral fins to effectively locomote on land (Standen et al, 2014). Erpetoichthys calabaricus has approximately twice as many precaudal vertebrae (100) as P. senegalus (45), while both genera have similar caudal vertebral numbers (Ward and Brainerd, 2007;Ward and Kley, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…These genera differ remarkably in body shape, although both are relatively elongate compared to other fishes. Erpetoichthys, commonly known as ropefish, has a serpentine-like body plan whereas all thirteen species of Polypterus are more stout-bodied (Brainerd et al, 1989;Ward and Brainerd, 2007;Ward and Kley, 2012). All Polypteriformes are facultative air breathers (Abdel Magid, 1967;Pettit and Beitinger, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…However, even though the precaudal vertebral region contributes more than the caudal region to axial lengthening, its evolution is also likely constrained because it is structurally linked to the abdominal cavity and digestive system. Changes in precaudal length are associated with changes in gut length and digestive efficiency (Ward and Kley ), and trade‐offs could potentially exist between mechanics of the precaudal axial skeleton and digestive function.…”
Section: Discussionmentioning
confidence: 99%
“…Body shape also has profound consequences for many aspects of fish biology, as it influences swimming kinematics and performance (Webb , ), habitat use (Nelson ; Yamada et al. ), as well as feeding physiology (Mehta and Wainwright ; Ward and Kley ) and behavior (Mehta et al. ).…”
mentioning
confidence: 99%
“…Intestine length has been found to vary substantially among fish species with different body shapes. A deeper‐body plan and a more elongate abdominal portion of the body maximizes the space in the abdominal cavity that can accommodate longer, more coiled guts (Montgomery 1977; Kramer and Bryant 1995; Ward and Kley 2012). This relationship between body shape and longer intestinal tracts has been found across disparate lineages of fishes, including neotropical freshwater fishes (Kramer and Bryant 1995) and marine stichaeoid (Barton 1982), and prickleback fishes (Montgomery 1977).…”
mentioning
confidence: 99%